An Unusual cause of Endocarditis. Issue 12 (21st December 2022) - Watkins, Rhys; Marincowitz, Carl; Locke, Thomas; Hunter, Steven
Abstract : A man in his 20s attended the emergency department with three days of fever, headache, reduced appetite and a sore throat. COVID-19 point-of-care test was negative. Blood cultures grew a gram-negative coccobacillus, Neisseria elongata . Following an episode of confusion, MRI head revealed septic emboli. Prolapse of the mitral valve with regurgitation was noted on echocardiography. Infection was found to have originated from multiple dental caries and treatment required a combination of dental extraction, prolonged antibiotic therapy and surgery for mitral valve repair. N. elongata is part of the normal oropharyngeal flora but is also a rare cause of endocarditis. There are no established treatment guidelines for endocarditis of this aetiology. N. elongata endocarditis may present atypically, with a murmur only developing several days later. 'Classical' stigmata should not be relied on to make a diagnosis. N. elongata predominantly affects the left side of the heart and predisposes to embolic events.